(untitled) (CIPEEX, 2025)
The present study evaluated the effects of a functional repatterning protocol on a professional Triathlon athlete, focusing on improving biomechanics and sports performance. The method involved applying interventions focused on postural correction, muscle strengthening, and increased mobility, conducted over five weeks with specific exercise sessions for swimming, cycling, and running. The biomechanical analysis compared kinetic and kinematic parameters before and after the intervention, using high-speed filming and force platforms. The results showed improvements in muscle strength, especially in the hip abductors and flexors, and in the range of motion of the hip and ankle joints, suggesting more efficient biomechanics and a possible reduction in injury risk. It is concluded that the functional repatterning protocol was effective in optimizing the athlete’s performance in Triathlon.